Floc Size Distributions of Cohesive Sediment in Homogeneous Isotropic Turbulence - Yu , Minglan; Yu, Xiao; Balachandar , S.; Manning , Andrew J. (Frontiers in Earth Science, 2022)
Floc size distribution is one of the key parameters to characterize flocculating cohesive sediment. An Eulerian-Lagrangian framework has been implemented to study the flocculation dynamics of cohesive sediments in homogeneous isotropic turbulent flows. Fine cohesive sediment particles are modeled as the dispersed phase by the discrete element method, which tracks the motion of individual particles. An adhesive contact model with rolling friction is applied to simulate the particle-particle interactions. By varying the physicochemical properties (i.e. stickiness and stiffness) of the primary particles, the dependence of the mathematical form of the floc size distribution on sediment properties is investigated. At the equilibrium state, the aggregation and breakup processes reach a dynamic equilibrium, in which construction by aggregation is balanced with destruction by breakup, and construction by breakup is balanced with destruction by aggregation. An equilibrium floc size distribution develops. When the primary particles are less sticky, a wide range of flocs are mainly constructed by aggregation of smaller flocs, the lognormal distribution performs better to describe the floc size distribution. When the primary particles are very sticky, both the aggregation of smaller flocs and breakup from larger flocs play an equally important role in the construction of the intermediate-sized flocs, the equilibrium floc size distribution can be better fitted by the Weibull distribution. When the Weibull distribution develops, a shape parameter around 2.5 has been observed, suggesting a statistically self-similar floc size distribution at the equilibrium state.